dévelloper reduire et ordonner les expressions suivantes A=(x-7)au carré - (x au carré -4x +4)

B=-9x(7x-2)+(21x-6)

C=(x-3)(x+3)+(4x+3)(x+1)

D=(8x+4)-(x-5)(2x+1)

E=(x+2)au carré -(x-3)au carré

F=5(2x-1)au carré-(6x+1)+3x(-2x+1)

1

Réponses

2012-10-29T14:39:56+01:00

A=(x-7)²-(x²-4x +4)=x²-14x+49-x²+4x-4=-10x+45

B=-9x(7x-2)+(21x-6)=-63x²+18x+21x-6=-63x²+39x-6

C=(x-3)(x+3)+(4x+3)(x+1)=(x²-9)+(4x²+4x+3x+3)=5x²+7x-6

D=(8x+4)-(x-5)(2x+1)=8x+4-(2x²+x-10x-5)=-2x²+17x+9

E=(x+2)²-(x-3)²=(x²+4x+4)-(x²-6x+9)=10x-5

F=5(2x-1)²-(6x+1)+3x(-2x+1)=5(4x²-4x+1)-6x²+3x=20x²-6x²-20x+3x+5=14x²-17x+5